Gas Adsorption Investigation on SiGe Monolayer: A First-Principle Calculation - Xiang Sun; Yuzheng Guo; Yan Zhao; Sheng Liu; Hui Li (Sensors, 2020)
The gas adsorption behaviors of CO, CO2, SO2, NO2, NO, NH3, H2, H2O, and O2 on SiGe monolayer are studied using the first-principles calculation method. Three special adsorption sites and different gas molecule orientations are considered. Based on adsorption energy, band gap, charge transfer, and the electron localization function, the appropriate physical adsorptions of SO2, NO, NH3, and O2 are confirmed. These gases possess excellent adsorption properties that demonstrate the obvious sensitiveness of SiGe monolayer to these gases. Moreover, SiGe may be used as a sensing material for some of them. NO2 adsorption in different adsorption sites can be identified as chemical adsorption. Besides, the external electric field can effectively modify the adsorption strength. The range of 0 ~ <semantics> − </semantics> 2 V/nm can create a desorption effect when NH3 adsorbs at the Ge site. The NH3 adsorption models on Ge site are chosen to investigate the properties of the I-V curve. Our theoretical results indicate that SiGe monolayer is a promising candidate for gas sensing applications.